Acute Kidney Injury is Associated with Worse Prognosis In COVID-19 Patients: A Systematic Review and Meta-analysis - Cheruiyot, Isaac; Henry, Brandon; Lippi, Giuseppe; Kipkorir, Vincent; Ngure, Brian; Munguti, Jeremiah; Misiani, Musa (Acta Biomedica Atenei Parmensis, 2020)
Background: The association between acute kidney injury (AKI) and outcome of coronavirus disease 2019 (COVID-19) has not yet been conclusively established. Therefore, we conducted a meta-analysis of recent scientific literature to assess whether AKI may be associated with worse prognosis and increased mortality in COVID-19 patients. Methods: A systematic search of literature was conducted between 1st November 2019 and 15th May 2020 on Medline (PubMed interface) and China National Knowledge Infrastructure (CNKI) to identify potentially eligible studies. Cohort or case-control studies reporting data on AKI in patients with or without severe COVID-19 were included. Studies were divided into separate cohorts for analysis based on two endpoints (severity [severe vs non-severe] and mortality [non-survivors vs survivors]). Data were pooled into a meta-analysis to estimate pooled odds ratio (OR) with 95% confidence interval (95% CI) for either outcome. Results: A total of 15 studies (n= 5,832 patients) were included in the analysis. Overall, AKI was found to be associated with significantly increased odds of COVID-19 severity (OR= 18.5; 95% CI 8.99-38.08) and mortality (OR= 23.9; 95% CI 18.84-30.31). No heterogeneity was observed for both outcomes (Cochran’s Q= 6.21, p=0.52, I2=0% and Cochran’s Q= 4.56, p=0.47, I2=0% respectively). -Conclusion: According to current data, AKI seems to be associated with worse prognosis in COVID-19 -patients. -Further investigation of the underlying mechanism of renal disease in COVID-19 would be needed to clarify possible therapeutic targets. AKI could be used as a clinical characteristic in severity classification and risk -stratification.